Valorization of natural tourism potentials in the Bihać tourism geographical region - Bidžan-Gekić, Aida; Gekić, Haris; Žunić, Lejla (Journal for Geography, 2019)
The Bihać tourism geographical region is rich in diverse, pollution-free, natural tourism potentials that can be the basis for the development of more specific forms of tourism (mountain, hunting, rural, excursion-recreational, adventure, recreational-sports, fishing and ecotourism) of local and regional as well as national and international significance. This paper will present the most important natural tourism potentials of the Bihać tourism geographical region, their valorization, as well as their possibility of exploitation for tourist purposes. Moreover, the tourist traffic and accommodation capacities of this tourism geographic region will be shown. Finally, it will be concluded how these unique still unpolluted natural phenomena should be treated in order for them to remain the same for future generations.